General english for aviation : pilots; cabin crew; ground staff; and air traffic controller - Uemura, Cintia Naomi (2014)
In this book. you will find: - easy-to-use ‘Warm-up and Pre-Listening’ or ‘Warm-up and Pre-Reading’ sections to help students to get acquainted with new vocabulary; - ‘Time to Practice 1’ and ‘Time to Practice 2’ to help students in the communication skill building; - ‘Drill Exercises’ to teach grammar structures easily and make students practice the vocabulary learned previously for each Unit; - a varied range of ‘Exercises’ for further grammar and vocabulary practices; - ‘Roleplay’ exercises that focus on the real-world communication in aviation to wrap-up all the grammar and vocabulary learned through the Unit; - the ‘Challenge’ section which provides the students the opportunity to express their own opinion and debate on the topics learned or use their creativity to reproduce or re-create the dialogues from the Unit; - an on-line audio material for the listening activities